Patient with Crouzon Syndrome Treated with Modified Le Fort III Osteotomy without Previous Orthodontic Treatment: Case Report and a Review of the Literature - Farnoosh Mohammadi; Afrooz Javanmard; Hamid Mojtahedi (Case Reports in Dentistry)
Crouzon syndrome is the most common type of craniofacial dysostosis anomaly which presents a great challenge for clinicians since birth. Multiple synostoses in the sutures of the cranial base in this syndrome result in the hypoplasia of the midface, shallow orbits, a short nasal dorsum, maxillary hypoplasia, and, in severe cases, obstruction of the upper airways. Apart from esthetic and functional problems, these patients suffer from various psychological problems which mandate correction of midface deformities at younger ages. The aim of this report is to describe the case of a 26-year-old female patient with Crouzon syndrome displaying severe midface hypoplasia and proptosis with no history of orthodontic treatment, who was treated with modified Le Fort III osteotomy with a coronal and intraoral approach without periocular incisions.